A Multitubular Kidney-on-Chip to Decipher Pathophysiological Mechanisms in Renal Cystic Diseases - Myram, Sarah; Venzac, Bastien; Lapin, Brice; Battistella, Aude; Cayrac, Fanny; Cinquin, Bertrand; Cavaniol, Charles; Gropplero, Giacomo; Bonnet, Isabelle; Demolombe, Sophie; Descroix, Stéphanie; Coscoy, Sylvie (Frontiers in Bioengineering and Biotechnology, 2021)
Autosomal Dominant Polycystic Kidney Disease (ADPKD) is a major renal pathology provoked by the deletion of PKD1 or PKD2 genes leading to local renal tubule dilation followed by the formation of numerous cysts, ending up with renal failure in adulthood. In vivo, renal tubules are tightly packed, so that dilating tubules and expanding cysts may have mechanical influence on adjacent tubules. To decipher the role of this coupling between adjacent tubules, we developed a kidney-on-chip reproducing parallel networks of tightly packed tubes. This original microdevice is composed of cylindrical hollow tubes of physiological dimensions, parallel and closely packed with 100 to 200 m spacing, embedded in a collagen I matrix. These multitubular systems were properly colonized by different types of renal cells with long-term survival, up to a couple of months. While no significant tube dilation over time was observed with Madin-Darby Canine Kidney (MDCK) cells, wild-type mouse proximal tubule (PCT) cells, or with PCT Pkd1+/- cells (with only one functional Pkd1 allele), we observed a typical 1.5-fold increase in tube diameter with isogenic PCT Pkd1-/- cells, an ADPKD cellular model. This tube dilation was associated with an increased cell proliferation, as well as a decrease in F-actin stress fibers density along the tube axis. Thanks to this kidney-on-chip model, we also observed that for larger tube spacing, PCT Pkd1-/- tube deformations were not spatially correlated with adjacent tubes whereas for shorter spacing, tube deformations were increased between adjacent tubes. Our device reveals the interplay between tightly packed renal tubes, constituting a pioneering tool well adapted to further study kidney pathophysiology.